Effects of high intensity intermittent training on lipid profile and blood glucose overweight/obese university students - Montealegre Suárez, Diana Paola; Ramos González, Edna Paola; Romaña Cabrera, Luisa Fernanda (Revista Cuidarte, 2022)
Highlights: Exercise is considered to have a protective effect on the health of all people Intermittent training of high intensity and continuous work of moderate intensity generate positive changes in the lipid profile High Intensity intermittent training causes glucose lowering in overweight and obese people High Intensity Interval Training (HIIT) is considered an important tool to combat obesity Introduction: High-Intensity Interval Training (HIIT) involves developing exercises in short periods of time with high intensity, followed by periods of rest between the series of exercises performed, and is considered an important tool to combat obesity. Therefore, the present work aimed to identify the effects of high-intensity intermittent training on the lipid profile in overweight and obese university students. Materials and methods: quasi-experimental study, consisting of a sample of 30 students, who were randomly assigned into two groups of 15 students, thus leaving a control group (continuous training): 15 and an experimental group (intermittent exercise of high intensity: 15. Moreover, there were carried out Laboratory tests before and after training to find the lipid profile. Also, the realization of 20 training sessions, which were distributed three times a week, with an average duration of 50 minutes. Additionally, the performed of statistical tests with a level of statistical significance of p <0.05. Results: there is a statistically significant relationship in the HDL value of the control and experimental group. The Glucose values show statistically significant relationships in the experimental group (p = 0.001). Conclusions: Intermittent high-intensity training and continuous moderate-intensity work generate a decrease in LDL and Triglycerides variables and an increase in HDL. However, they are not statistically significant after 20 training sessions. However, high-intensity intermittent training results in glucose-lowering in overweight and obese people. How to cite this article: Montealegre Suárez Diana Paola, Ramos González Edna Paola, Romaña Cabrera Luisa Fernanda. Effects of high intensity intermittent training on lipid profile and blood glucose overweight/obese university students. Revista Cuidarte. 2022;13(3):e2624. http://dx.doi.org/10.15649/cuidarte.2624